2014
DOI: 10.1177/0954405414539934
|View full text |Cite
|
Sign up to set email alerts
|

Using Mahalanobis–Taguchi system, logistic regression, and neural network method to evaluate purchasing audit quality

Abstract: The feature selection function in data mining facilitates the classification of vast data volumes and reduces attribute variables, enabling the construction of classification prediction models. For binary data, the Mahalanobis-Taguchi system, the logistic regression method, and the neural network method all feature high stability and accuracy. The MahalanobisTaguchi system differs from the other two methods in that models are developed through a measurement scale rather than from the learning of analytical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…However, it is difficult to conduct a systematic analysis of the regional transport market to uncover the impact of the THSR simply by examining changes in the market share of different modes [5,28]. Therefore, it is necessary to apply our model to better understand the dynamic rivalry between THSR and the conventional rail and air transport in Taiwan from a regional market point of view [29][30][31][32][33][34]. From the analysis based on the model, we can reveal the trend of influence between transport modes, and these findings can be utilized as forecasting references [35][36][37][38][39].…”
Section: Empirical Study and Data Collectionmentioning
confidence: 99%
“…However, it is difficult to conduct a systematic analysis of the regional transport market to uncover the impact of the THSR simply by examining changes in the market share of different modes [5,28]. Therefore, it is necessary to apply our model to better understand the dynamic rivalry between THSR and the conventional rail and air transport in Taiwan from a regional market point of view [29][30][31][32][33][34]. From the analysis based on the model, we can reveal the trend of influence between transport modes, and these findings can be utilized as forecasting references [35][36][37][38][39].…”
Section: Empirical Study and Data Collectionmentioning
confidence: 99%
“…In this section, we study the impact of qualitative improvements in financial development on firms' R&D and further discuss the impact of financial development on the allocation efficiency of firms' R&D [37][38][39][40][41][42][43]. Therefore, we use firm R&D as the explained variable, the qualitative indicators of financial development (financial efficiency, financial competition) as the threshold variables of financial scale development, and enterprise heterogeneity (total factor productivity) and the other variables as explanatory variables [44][45][46][47][48][49][50].…”
Section: Measurement Model Construction and Inspectionmentioning
confidence: 99%
“…The Mahalanobis distance of a product from an abnormal sample that is calculated using the means, standard deviations, and correlation coefficient inverse matrices of base space is extremely high. Additionally, thresholds can be determined using the smallest type-I error (normal products misjudged as abnormal products) and type-II errors (abnormal products misjudged as normal products) that occur [15,16].…”
Section: Mtsmentioning
confidence: 99%
“…Nevertheless, the MTS method features high stability and an accuracy rate higher than 98%. Thus, the MTS, which involves using data mining and classification methods to reduce attribute variables for building prediction models, demonstrates high discrimination ability in practice [16]. The type-I errors (i.e., the analysis methods showed that tablet PCs were abnormal products when in fact they were normal products), and type-II errors (i.e., the tablets PCs were abnormal products that failing to judge as normal products) were identified for each method.…”
Section: Neural Network Analysismentioning
confidence: 99%